Psychological Security and its Relationship with Professional Performance Among Primary Education Teachers in the Zakho Independent Administration - Mohammed, Haifa Wahid (Al Irsyad: Jurnal Studi Islam, 2025)
TTeachers' psychological security impacts educational quality, yet few studies examine its relationship with professional performance in Kurdistan's educational context. This study investigates the relationship between psychological security and professional performance among Zakho's basic education teachers across various demographic factors. Using correlational-descriptive approaches, 100 randomly selected teachers completed Maslow's Security Scale and a standardized Professional Performance Scale with five-point measurements. Results revealed high levels of psychological security and professional performance among teachers. Statistical analysis showed no significant differences in psychological security across gender, age, or years of service. However, professional performance varied significantly with years of service, with teachers having 31-40 years of experience demonstrating superior performance compared to other groups. The study established a significant positive correlation (r=0.512, p<0.01) between psychological security and professional performance, indicating that teachers with stronger psychological security tend to demonstrate more effective professional performance in educational settings. Enhancing teachers' psychological well-being represents a crucial strategy for improving teaching effectiveness and educational quality in basic education